2014
DOI: 10.1016/j.ajpath.2014.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Homeostasis Is Altered in Skeletal Muscle of Spontaneously Hypertensive Rats

Abstract: Hypertension is often associated with skeletal muscle pathological conditions related to function and metabolism. The mechanisms underlying the development of these pathological conditions remain undefined. Because calcium homeostasis is a biomarker of muscle function, we assessed whether it is altered in hypertensive muscles. We measured resting intracellular calcium and store-operated calcium entry (SOCE) in fast- and slow-twitch muscle fibers from normotensive Wistar-Kyoto rats and spontaneously hypertensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…In line with previous studies, EDL fast‐twitch skeletal muscle fibres of adult control rats showed a value of resting [Ca 2+ ] i of 29.7 ± 1.9 nM. Cisplatin administration was associated with a significant alteration of resting [Ca 2+ ] i .…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…In line with previous studies, EDL fast‐twitch skeletal muscle fibres of adult control rats showed a value of resting [Ca 2+ ] i of 29.7 ± 1.9 nM. Cisplatin administration was associated with a significant alteration of resting [Ca 2+ ] i .…”
Section: Resultssupporting
confidence: 90%
“…To test the functional status of SOCE in muscles of the different animal groups, we used Mn 2+ quenching of Fura‐2 fluorescence after SOCE activation. To this end, SR Ca 2+ stores of muscle fibres were depleted with thapsigargin and caffeine . As shown in Figure A and 5B, EDL muscle of cisplatin treated rats displays a significantly reduced Mn 2+ entry rate compared with that of control animal, indicating that SOCE induced by SR Ca 2+ depletion is compromised in cachectic muscle.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations